Perceived accessibility, and adequacy of COVID-19 related information in Nigeria - Chinenye I. Ubah; Linda Odikpo; Lovelyn Ndubuisi-Okoroezi; Chisom Mbadugha; Jennifer Ikechukwu-Okoroezi (AOSIS, 2022)
Information on COVID-19 has evolved and blended with fake news, which the public, unfortunately, has to make an individual decision on how to use. As a result, access to authentic and adequate health information on COVID-19 is crucial for curbing the ongoing pandemic. The study was aimed at identifying sources of information on COVID-19 commonly used by adult Nigerian residents; determine the adequacy of information received; determine the accessibility of information on COVID-19 among Nigerians, and explore the relationship between location and access to information. An adapted version of the World Health Organization's (WHO) COVID-19 behavioral insight questionnaire was used to collect data from 1,039 adult residents in Nigeria across the geopolitical zones through an online survey. Analysis was done using SPSS version 24. Logistic regression was used to examine if location predicts access to information. Social media was identified as the major source of information among Nigerians. The top three accessible sources included social media 807(77.7%), television 546 (52.6%), and WHO websites 340 (32.7%). It was also found that they perceived information received on COVID-19 as adequate. The logistic regression model of the location did not predict access to COVID-19 information (p0.05; 95% CI). Health authorities like the WHO, the ministry of health, CDC should optimize social media for better health information coverage.